ANALISIS DAMPAK PENETRASI TINGGI PLTS TERHADAP RESPONS FREKUENSI PADA SISTEM TRANSMISI INTERKONEKSI - Nurul Muhammad Farouq; Nurmela (PT. Hasba Edukasi Mandiri, 2026)
The integration of Solar Photovoltaic (PV) power plants into power systems has become one of the main strategies to support Indonesia’s energy transition targets as outlined in the 2025–2034 Electricity Supply Business Plan (RUPTL). One of the planned projects is a 126 MW PV power plant that will be connected to the 150 kV Central Kalimantan transmission system. Although it increases the utilization of renewable energy, high PV penetration may affect system frequency response due to the reduced contribution of synchronous generator inertia. This study aims to analyze the impact of PV integration on system frequency response using Root Mean Square (RMS) simulations in DIgSILENT PowerFactory. The evaluation was conducted through PV disconnection scenarios at penetration levels of 25%, 50%, 75%, and 100%, as well as the outage of the largest generating unit. The results show that increasing PV penetration decreases the frequency nadir from 49.944 Hz to 49.778 Hz and increases the Rate of Change of Frequency (RoCoF) from 0.530 Hz/s to 2.154 Hz/s. In the largest generator outage scenario, RoCoF increases from 1.199 Hz/s to 1.257 Hz/s without significant changes in the other frequency response parameters. The results indicate that the integration of the 126 MW PV power plant can still be accommodated by the 150 kV Central Kalimantan system without significant degradation of frequency response performance.